Pulmonary Combined Large Cell Neuroendocrine Carcinoma - Meihui Li; Meihui Li; Meihui Li; Meihui Li; Lan Yang; Lan Yang; Lan Yang; Hongyang Lu; Hongyang Lu; Hongyang Lu (Frontiers Media S.A., 2022)
Pulmonary combined large-cell neuroendocrine carcinoma (CLCNEC) is a rare neuroendocrine tumor pertained to lung large cell neuroendocrine carcinoma (LCNEC) with aggressive behavior and poor prognosis generally. The clinical features of CLCNEC are not specific including cough, expectoration, chest distress, chest pain, etc., which are prone to have different manifestations of the mixed components. Owing to the low incidence, there are few related small-scale retrospective studies and case reports. Currently, the treatment regimen of CLCNEC mainly refers to LCNEC that complete surgical resection is preferred in the early stage and according to previous researches, platinum-based small cell lung cancer (SCLC) standard treatment regimen showed promising results in postoperative and advanced CLCNEC as compared to that of non-small cell lung cancer (NSCLC). Adenocarcinoma-CLCNEC more likely harbor driver gene mutation, and may benefit from targeted therapy. As for immunotherapy, more clinical trial data are needed to support its benefits. This article will fill the gap and will provide new insight into the clinical characteristics, pathological diagnosis and treatment endeavors of CLCNEC.